2 - Re-inventing Federalism in Post-Transition Nigeria: Problems and Prospects: DOI: 10.4314/ad.v29i2.22192 - Agbu, Osita (Africa Development, 2004)
This paper grapples with the question of Nigeria's federal practice. It argues that there is a need to re-examine federalism in the country with a view to restructuring the system so that it reflects the ethnological and political realities on the ground. It proposes the de-concentration or decentralisation of the powers of the central government, which increased astronomically during military rule to the disadvantage of the component units—the states. In addressing this subject matter, the paper critically examines the theoretical basis for the notion of federalism, seeking to determine Nigeria's suitability as a federal state in the first instance. A historical overview of the origin of Nigeria's federalism— alongside a discussion of present-day predicaments—is presented in the preliminary analysis. Subsequently, the persisting problems in Nigeria's federalism—like the monopoly of state power, revenue allocation, state creation and federal character—are re-visited with a view to determining the situation in the post-transition democratic environment. Finally, the paper makes a case for the constitutional division of the country into geo-political zones, the rotation of power amongst these zones, and the decentralisation of power away from the centre ft) the states and local governments.